GROUP GUIDANCE WITH COMPUTATIONAL RIGOROUS MATHEMATICAL THINKING (CRMT) MODEL TO IMPROVE STUDENTS’S ASSERTIVE COMMUNICATION - Barida, Muya; Sari, Utari Dwi Perwita; Hartanto, Dody; Widyastuti, Dian Ari; Rofiah, Nurul Hidayati; Andriyani, Andriyani (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
Assertive communication is needed to create comfort in communicating, feelings of mutual respect between individuals, avoiding passive and aggressive communication, and maintaining rights between individuals. This research aims to test the effectiveness of group guidance using the Computational Rigorous Mathematical Thinking (CrmT) model in improving assertive communication. To achieve this goal, the research used a pre-experimental research design. The research subjects were selected using a purposive sampling technique, namely six students of class VIII-E at SMP Negeri 1 Wanareja. Furthermore, data were collected using an assertive communication scale instrument and analyzed using the T-Test formula. The results of the research show that the group guidance of the Computational Rigorous Mathematical Thinking model is effective in improving students' assertive communication